2013
DOI: 10.1017/s1049023x13003543
|View full text |Cite
|
Sign up to set email alerts
|

Crew and Patient Safety in Ambulances: Results of a Personnel Survey and Experimental Side Impact Crash Test

Abstract: The crash test demonstrated a lack of safety for EMS personnel and patients in the rear compartment. It would be preferable if each piece of medical equipment were provided with a quick release system resistant to three-dimensional 10G forces. The kinetic changes undergone by the "patient" substitute on the stretcher would probably have an effect of causing injury pathology. This study highlights the need for more research and development in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Care equipment must be of high quality and it should be tested at the beginning of each shift. The importance of maintaining high quality in emergency care equipment has been observed before [10,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Care equipment must be of high quality and it should be tested at the beginning of each shift. The importance of maintaining high quality in emergency care equipment has been observed before [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on medication errors have shown that risks were caused by overdosing or administering a wrong drug [8,9]. Further studies reveal that patient safety is associated with staff competence [10][11][12]. Besides clinical competence, emergency care providers need situational sensitivity and problem-solving skills.…”
Section: Introductionmentioning
confidence: 99%
“…Emergency care workers are expected to be able to identify, analyse and act on deteriorating patients, near-misses and potential adverse events. Keeping up-to-date by means of continuing education is part of competence [11][12][13][14]. Competence in process and risk management is also necessary [1] and situation-sensitivity required to prevent near misses and adverse events [1, 15,16].…”
Section: Clinical Competence and Skill Definedmentioning
confidence: 99%
“…Some threats are technical, related to e.g. stretcher issues [ 9 ], crash related issues [ 10 ] or the introduction of new technology [ 11 ]. Frequent handovers between the different EMS organizations may also cause miscommunications and adverse events [ 12 ].…”
Section: Introductionmentioning
confidence: 99%